Assessment of the structural integrity of cracked cylindrical geometries applying the EVTUBAG program. - Hernández Gómez, Luis Héctor; Urriolagoitia Calderón, Guilllermo; Urriolagoitia Sosa, Guillermo; Sandoval Pineda, Juan Manuel; Merchán Cruz, Emmanuel Alejandro; Guardado García, José Francisco (Rev. Téc. Fac. Ing. Univ. Zulia, 1970)
In this paper, the assessment of the structural integrity of pressurized cylindrical components containing defects like cracks was performed, considering two types of failures. Brittle failure was evaluated considering Fracture Mechanics and ductile failure was calculated with a plastic analysis. For this purpose, three methods were used. Accordingly, the program EVTUBAG (evaluation of cracked pipe by its initials in Spanish) was written considering the methodologies proposed by Ruiz and Corran, ASME and Raju-Newman. This paper describes this program and relevant results are discussed.